EVALUATION MODEL FOR SECURITY COMPONENTS: A CASE STUDY ON MALAYSIAN INTERNET BANKING - Ahmad, R. (2011)
ABSTRACT. The usage of Internet Banking in Malaysia, which started about 10 years ago, has been well accepted by consumers. Statistics from Bank Negara Malaysia (BNM) show that every year there is an increase in the number of registered individual Internet banking users since its inception in Malaysia. As at the third quarter of 2010, there were approximately 9.2 million registered Internet Banking users compared to only 2.6 million in 2005. A survey of 264 CIMB Bank Berhad personnel revealed that although there is a high degree of confidence, with respondents claiming to be aware of requirements by the bank, further and thorough inspections suggest that there are several areas in which desirable knowledge and understanding are still lacking. Additionally, in order to identify the currents state of the security features offered, we performed an analysis of six (6) Internet Banking websites in Malaysia. Using the evaluation model proposed in this study, an analysis of Internet banking website security elements revealed that there is still room for improvement in areas such as helping users to execute transactions and create awareness on their responsibilities as outlined by the banks.